The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5606/tftrd.2017.333
|View full text |Cite
|
Sign up to set email alerts
|

Side differences of the lateral abdominal wall in supine rest position in mild adolescent idiopathic thoracolumbar scoliosis

Abstract: Objectives: This study aims to evaluate the thickness of the abdominal muscles on both sides in patients with mild adolescent idiopathic scoliosis (AIS) and to assess the absolute and relative thickness of oblique external (OE), oblique internal (OI), and transversus abdominis (TrA). Patients and methods: A total of 84 participants underwent ultrasonographic examination of the abdominal muscles in the supine resting position. All participants were divided into two groups including AIS group (n=42) and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…For the last few decades, B-mode ultrasound imaging (USI) has been used to assess muscles' geometry. In some cases, USI has been used to assess lateral abdominal muscles (LAMs) thickness or thickness change at rest and during various movements because the potential role of LAM in low back pain (LBP) [1][2][3] and scoliosis [4][5][6][7][8][9][10][11] was verified. Recently, quantitative shear wave ultrasound elastography (SWE) has also been developed and used to study muscle shear modulus [12] and refer it to muscles' elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…For the last few decades, B-mode ultrasound imaging (USI) has been used to assess muscles' geometry. In some cases, USI has been used to assess lateral abdominal muscles (LAMs) thickness or thickness change at rest and during various movements because the potential role of LAM in low back pain (LBP) [1][2][3] and scoliosis [4][5][6][7][8][9][10][11] was verified. Recently, quantitative shear wave ultrasound elastography (SWE) has also been developed and used to study muscle shear modulus [12] and refer it to muscles' elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kim et al 5 have shown no differences in LAM thickness between IS and control group, and Yang et al 4 have observed thicker OE muscle on the convex body side compare to concave side in IS. In contract, some studies have shown no side-to-side asymmetry of all LAM in IS patients 6,26 . In general, there are no consistent observations on LAM side-to-side asymmetry in studies on healthy adolescents [27][28][29] , and it is suggested that the symmetry of LAM depends on the biomechanics during sport's practice in athletes 28,29 .…”
Section: Discussionmentioning
confidence: 96%
“…In turn, elasticity analysis within the scoliosis group showed: (a) no significant asymmetry in LAM elasticity between convex and concave body sides; (b) the TrA during isometric contraction was stiffer in the lumbar subgroup compared to thoracic and thoracolumbar subgroups. www.nature.com/scientificreports/ www.nature.com/scientificreports/ In the literature, there are some studies comparing LAM thickness in IS with non-IS controls and/or considering LAM thickness side-to-side asymmetry (convex vs. concave) only in IS group [4][5][6][7]12,26 . The results of the presented study demonstrated that LAM thickness at rest was similar in IS and non-IS groups, but side-to-side asymmetry of the OE muscle at rest and during isometric contraction was only detected in IS group (left side thicker).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the bone and ligament system as well as the muscular system affect proper shaping of body posture. According to Linek et al, weakness as well as improper functioning of muscles may contribute to the formation of spine deformities (29).…”
Section: Discussionmentioning
confidence: 99%